2016
DOI: 10.1371/journal.pone.0160540
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs and Attitudes of Patients and the General Public towards the Interactions of Physicians with the Pharmaceutical and the Device Industry: A Systematic Review

Abstract: ObjectiveTo systematically review the evidence on the knowledge, beliefs, and attitudes of patients and the general public towards the interactions of physicians with the pharmaceutical and the device industry.MethodsWe included quantitative and qualitative studies addressing any type of interactions between physicians and the industry. We searched MEDLINE and EMBASE in August 2015. Two reviewers independently completed data selection, data extraction and assessment of methodological features. We summarized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 61 publications
1
50
0
1
Order By: Relevance
“…On the other hand, DeGeorge et al 33 found that studies that report conflict of interest are more likely to show a favorable outcome regarding infections (p<0.01), wound complications (p<0.01), overall morbidity (p<0.07) and mortality (p<0.05). 33 Finally, the review by Fadlallah et al 41 showed that patients and the general public care very little about the personal gifts their physicians receive from the pharmaceutical industry, and that when studies focus on surgeons, patients believe that professionals decide what is best for their health, regardless of their financial relationship with the industry.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, DeGeorge et al 33 found that studies that report conflict of interest are more likely to show a favorable outcome regarding infections (p<0.01), wound complications (p<0.01), overall morbidity (p<0.07) and mortality (p<0.05). 33 Finally, the review by Fadlallah et al 41 showed that patients and the general public care very little about the personal gifts their physicians receive from the pharmaceutical industry, and that when studies focus on surgeons, patients believe that professionals decide what is best for their health, regardless of their financial relationship with the industry.…”
Section: Discussionmentioning
confidence: 99%
“…A study (Fadlallah et al, 2016) found that participants’ awareness on physician’s receipt of gifts was low. It also reported less concern, lower awareness and more acceptance of surgeon-device industry relative to physician-pharmaceutical industry interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, others view the opposing logics in both organizations as insurmountable and suggest that interactions between pharmaceutical companies and healthcare providers are primarily geared towards promoting the products of the pharmaceutical company, which conflicts with the social responsibility of healthcare providers. Empirically, studies find that interaction between pharmaceutical companies and healthcare providers could result in a conflict of interests (COI), negatively alter physicians’ prescribing behavior, or result in a negative perception towards professionals [ 22 , 29 35 ]. As a result, several guidelines have been created to help professionals navigate the opposing explanations of interactions with pharmaceutical companies [ 36 38 ].…”
Section: Introductionmentioning
confidence: 99%